FIRST ZOEAL STAGE and MEGALOPA of UCA (UCA) MARACOANI (DECAPODA: BRACHYURA), WITH COMMENTS on THE LARVAL MORPHOLOGY of SOUTH-AMERICAN SPECIES of OCYPODIDAE - Negreiros-Fransozo, Maria L. [UNESP]; Hirose, Gustavo L. [UNESP]; Fransozo, Adilson [UNESP]; Bolla, Eduardo A. [UNESP] (Crustacean Soc, 2009)
Odn the Brazilian coast, ten species of fiddler crabs occur in the estuaries and mangrove systems. The larval development of only five of these species is completely known. Here we describe the first zoeal stage and megalopa of Uca (Uca s. str.) maracoani. Ovigerous females and megalopae were obtained at Jabaquara Beach, Paraty, state of Rio de Janeiro, Brazil. The first zoeal stage was obtained from ovigerous females in the laboratory, and the megalopae directly from the field. Both zoeae and megalopae were raised in laboratory conditions. The megalopae survived until the eighth juvenile stage, when they could be identified to species. The larval morphology was analyzed and compared with the species already known for the Brazilian coast, and some other species, such as the southeast Atlantic fiddler crab, Uca tangeri. The comparison showed that U. maracoani has some characteristics that are more similar to U. tangeri than the previously studied species from the Brazilian coast. This is the first description of the zoea and megalopa morphology of a member of the genus Uca from the southwest Atlantic, of which the adult has a narrow front sensu Crane (1975), and it is helpful for taxonomic, systematic and ecological purposes.
Keywords: Brazilian coast; fiddler crab; larval morphology; Ocypodidae; Uca